Gibson's paradox and the natural rate of interest - Luca Benati; Pierpaolo Benigno (University of Bern, Department of Economics, 2023)
We argue that Gibson's paradox has nothing to do with the Gold Standard per se, and it rather originates from low-frequency variation in the natural rate of interest under certain types of monetary regimes that make inflation I(0) and (approximately) zero-mean. Although the Gold Standard is the only historical example of such a regime, Gibson's paradox is a feature of a potentially wide array of monetary arrangements. In fact, once removing the deterministic component of the drift in the price level, the paradox can be recovered from the data generated under inflation-targeting regimes. By the same token, the paradox could arise under a regime targeting the level of the money stock, whereas it would not appear under arrangements targeting the levels of either prices or nominal GDP. We show that the mechanism underlying Gibson's paradox hinges on the interaction between the Fisher equation and an asset pricing condition determining the current value of money. Our interpretation points towards inefficiencies in the actual implementation of monetary policies.
Keywords: E2; E3; 330; Gibson's Paradox; monetary regimes; natural rate of interest; Fisher equation; Gold Standard; inflation targeting; optimal monetary policy